A Commentary on the 23rd International Meeting of Communist and Workers’ Parties (World Marxist Review, 2024)
The 23rd International Meeting of Communist and Workers’ Parties was held on 19-22 October 2023 in Izmir, Turkey. It was held against the background of the deepening crisis of capitalism, the continuous outbreak of regional wars, the rise of social and workers’ movements, the relentless increase in anti-communist activities, the convening of congresses by new parties, and the success of some political parties in the elections. The meeting explored issues arising from the current regional wars, expressed solidarity with the world socialist and anti-imperialist movements, discussed the new requirements of ideological struggle in a field changed by capitalist information technology, and finally formulated a joint action plan. The international meeting embodied the spirit of internationalism among the various communist and workers’ parties, but at the same time it also revealed certain conflicts and differences.